EFEKTIVITAS FUNGSI PENGAWASAN INSPEKTORAT TERHADAP KINERJA PEGAWAI ( STUDI KASUS BADAN KEPEGAWAIAN DAN DIKLAT KABUPATEN OGAN KOMERING ILIR TAHUN 2016) - Nabilah Nabilah; Rendy Sueztra Canalldhy (Jurnal Pemerintahan dan Politik, 2019)
The results of this study indicate that the function of OKI's inspectorate supervision on the performance of BKD OKI which has not been effective. This is due to its non-fulfillment of elements associated with Stoner's theory of Accurate, timely, focused on strategic monitoring points. Where BKD data at the time of collecting documents is incomplete as well as the existence of delays. The data that has not been completed by BKD is LP2P data and SOP. As well as in conducting inspection inspectorate apparatus has not determined the areas of irregularities that often occur, so that the impact is not corrective in performing performance in the BKD. Factors that affect the implementation of the inspectorate supervision of the performance of Personnel and Training Agency OKI Regency is an internal factor, namely as the supervisory apparatus and external factors, that are facilities and infrastructure and some negligence by the object inspectionKeywords : Effectiveness, Supervision, Inspectorate, BKD